Hurricane - Chin, Jason, 1978- (Neal Porter Book, Holiday House, 2025)
"It's a beautiful day on Hatteras Island, North Carolina. But while all seems calm now, a hurricane is brewing out at sea, and everyone is wondering if it will reach the coast--and where. Is Hatteras in its path? Night and day, meteorologists track the storm. Brave pilots fly straight into it to gather urgent data. Back on the island, as the hurricane moves closer, families board up windows, stock emergency supplies, and do all they can to prepare."--